Geothermal flux and basal melt rate in the DomeÂ C region inferred from radar reflectivity and heat modelling - Olivier Passalacqua; Catherine Ritz; Frédéric Parrenin; Stefano Urbini; Massimo Frezzotti (The Cryosphere, 2017)
Abstract. Basal melt rate is the most important physical quantity to be evaluated when looking for an old-ice drilling site, and it depends to a great extent on the geothermal flux (GF), which is poorly known under the East Antarctic ice sheet. Given that wet bedrock has higher reflectivity than dry bedrock, the wetness of the ice–bed interface can be assessed using radar echoes from the bedrock. But, since basal conditions depend on heat transfer forced by climate but lagged by the thick ice, the basal ice may currently be frozen whereas in the past it was generally melting. For that reason, the risk of bias between present and past conditions has to be evaluated. The objective of this study is to assess which locations in the Dome C area could have been protected from basal melting at any time in the past, which requires evaluating GF. We used an inverse approach to retrieve GF from radar-inferred distribution of wet and dry beds. A 1-D heat model is run over the last 800 ka to constrain the value of GF by assessing a critical ice thickness, i.e. the minimum ice thickness that would allow the present local distribution of basal melting. A regional map of the GF was then inferred over a 80 km × 130 km area, with a N–S gradient and with values ranging from 48 to 60 mW m−2. The forward model was then emulated by a polynomial function to compute a time-averaged value of the spatially variable basal melt rate over the region. Three main subregions appear to be free of basal melting, two because of a thin overlying ice and one, north of Dome C, because of a low GF.